IMMUNOMODULATION MECHANISM BY GOLD NANOPARTICLES FOR CANCER THERAPY - Salma Hamdan; Bassam Al Khouri; Rami Hariri (Journal of Biomedical and Techno Nanomaterials, 2025)
Conventional cancer treatment is often limited by side effects and resistance to therapy. Therefore, immunotherapy research, especially those involving gold nanoparticles (AuNPs), is growing as a more effective and specific therapeutic alternative. AuNPs have the potential to modulate the body's immune response, improving the recognition and destruction of cancer cells by the immune system. This study aims to investigate the immunomodulation mechanisms triggered by AuNPs and evaluate their potential as cancer therapeutic agents by increasing immune cell activity and cytokine production. This study used cell culture to test the effects of AuNPs on the activity of T cells, macrophages, and dendritic cells as well as the production of cytokines IL-2, TNF-?, and IL-12. Gold nanoparticles were applied at various concentrations (5, 10, 20 ?g/ml) and treatment times (24, 48, 72 hours), then measured using flow cytometry and ELISA. The results showed that AuNPs increased the activity of immune cells, especially dendritic cells, macrophages, and T cells, as well as the production of cytokines IL-2, TNF-?, and IL-12. This increase in immune cell and cytokine activity is directly related to the concentration and duration of AuNPs treatment. This study shows that AuNPs can modulate the body's immune system and increase the immune response to cancer. Gold nanoparticles have the potential as immunomodulatory agents in more effective and safe cancer therapy. More research is needed to confirm these findings in animal and human models.